The Influence of Board Gender Diversity on Non-financial Reporting Compliance: Evidence from Portuguese Listed Companies - Sónia MONTEIRO; Kátia LEMOS; Lénia PEREIRA; Verónica RIBEIRO (Communications of International Proceedings, 2021)
Research Question: The aim of this paper is to analyse the influence of board gender diversity on the level of non-financial reporting compliance, imposed by the the Portuguese Decree-Law (DL) nº 89/2017, considering a sample of Portuguese  listed companies. As methodology  we used a content analysis of non-financial information published in the first mandatory period for the adoption of DL 89/2017. Research Findings: The results show a high degree of compliance with regulation and that the level of non-financial disclosure is positively associated with female presence on boards. Theoretical/Academic Implications: This study differs from and extends prior research. To the best of our knowledge, this study provides a first insight at the influence of the board gender diversity on mandatory non-financial reporting. Practitioner/Policy Implications: This study helps to highlight the importance of women on boards' role in increasing transparency and ensuring the quality and compliance of non-financial reports. Thus, our findings could have implications for policy formulation, to encourage board gender diversity and its effects on non-financial reporting quality.
Keywords: Women on boards; Board gender diversity; Non-financial Reporting; Mandatory disclosure; Directive 2014/95/EU; Decree-law No. 89/2017